2022
DOI: 10.1111/jonm.13549
|View full text |Cite
|
Sign up to set email alerts
|

Quality and efficiency of a standardized e‐handover system for pediatric nursing: A prospective interventional study

Abstract: Aim This study examined the effect on pediatric nursing handover quality and efficiency when a standardized e‐handover system was implemented. Background Handover quality is an important aspect of nursing quality management; however, handover quality among nursing staff is poor. Methods A prospective interventional study was carried out in a general pediatrics ward from December 2019 to November 2020. The tools included a standardized e‐handover system. The intervention strategies included workflow remodeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It also aimed to boost interactive communication which promotes guiding and ensures systematic assessment of nursing students during clinical training. The research (9) addressed the difficulties cited in clinical training, they sought to create guiding and evaluation uses. With this application, nurse education in medical training was meant to be more adaptable, high-quality, and effective.…”
Section: Introductionmentioning
confidence: 99%
“…It also aimed to boost interactive communication which promotes guiding and ensures systematic assessment of nursing students during clinical training. The research (9) addressed the difficulties cited in clinical training, they sought to create guiding and evaluation uses. With this application, nurse education in medical training was meant to be more adaptable, high-quality, and effective.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Moreno‐Fergusson et al (2021) stated that conducting AI prescriptive and predictive analytics improves inpatient care management and reduces nurse workload. Zhou et al (2022) applied an AI standardized electronic handover system that has great potential for improving paediatric patient safety and the quality of handovers. Liu et al (2022) reported that AI technology‐based medical information processing can be applied to emergency first aid nursing management.…”
Section: Introductionmentioning
confidence: 99%